Electrocatalytic Water Splitting and CO2 Reduction: Sustainable Solutions via Single‐Atom Catalysts Supported on 2D Materials. Issue 9 (26th February 2019) - Kwon, Ki Chang; Suh, Jun Min; Varma, Rajender S.; Shokouhimehr, Mohammadreza; Jang, Ho Won
Abstract: Single‐atom catalysts (SACs) have been garnering attention recently due to their excellent performance in significant catalytic reactions such as oxidation, water gas shift, and hydrogenation reactions. Unlike traditional nanocatalysts, the catalytic performance of SACs is highly dependent on the scale of catalysts, low‐coordination nature, and interaction between the catalysts and support materials. The size of metal particles is a key factor in determining the performance of the catalysts as the specific activity per metal atom usually increases with decreasing size of metal particles; the small size of metal particles serves as the catalytically active sites. Furthermore, the support materials should have not only an extremely large surface area to host a lot of catalysts in their structures, but also the ability to capture the catalysts appropriately. 2D materials, which have a high specific surface‐to‐volume ratio and van der Waals forces to capture catalysts, have been considered good support materials. A detailed discussion on the preparation, characterization, and catalytic performance, especially for water splitting and carbon dioxide utilization reactions using SACs supported on 2D materials, is provided; the main advantages of SACs and the associated challenges for improving their catalytic performance are highlighted. Abstract : Single‐atom catalysts (SACs) supported on 2D materials are reviewed with a detailed discussion on the preparation, characterization, and catalytic performance, especially for water splitting and carbon dioxide utilization reactions using SACs supported on 2D materials. The main advantages of SACs and the associated challenges for improving their catalytic performance are also highlighted.